2023
DOI: 10.1039/d3nj02509h
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental nature and importance of electrostatic potential in hydrogen bond formation: a case study of heterocycles frequently observed in drugs

Mambatta Haritha,
Cherumuttathu H. Suresh

Abstract: Molecular electrostatic potential (MESP) analysis is employed to predict the hydrogen bond (HB) interaction strength (Eint) of frequently encountered chemical motifs (CO‾‾‾HC, CN‾‾‾HN, CN‾‾‾HC, CF‾‾‾HC, and CN‾‾‾OC) in commonly observed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In our prior studies, we successfully forecasted hydrogen bond strengths between water and various chemical motifs, utilizing reference molecules representing each motif, selected for their simplicity and appropriateness. 38,42 Fig. 1 shows twenty ring molecules, each incorporating distinct chemical motifs such as CO — HC, CO — HN, N — HC, CN — HN, F — HC, N — OC, Br — HC, S — HC, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our prior studies, we successfully forecasted hydrogen bond strengths between water and various chemical motifs, utilizing reference molecules representing each motif, selected for their simplicity and appropriateness. 38,42 Fig. 1 shows twenty ring molecules, each incorporating distinct chemical motifs such as CO — HC, CO — HN, N — HC, CN — HN, F — HC, N — OC, Br — HC, S — HC, etc.…”
Section: Resultsmentioning
confidence: 99%
“…33 Utilizing the outer contour of electronic density in conjunction with MESP parameters is an approach to elucidate the properties of non-covalent interactions across various studies. 34–39 Politzer et al revealed that the computed electrostatic potentials for aqua metal complexes offer valuable insights into the strength of hydrogen bonds. 40 Zarić et al employed accurate quantum chemical calculations to evaluate the strength of hydrogen bond interactions in coordinated ethylenediamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Surprisingly, compound A6 had eight HBAs (no more than 10) and four HBDs (no more than five), which complied with the Ribinski rule. 45 Therefore, compound A6 can be used as a promising candidate for the development of new antiviral drugs targeting TMV CP. TEM Determination of Compounds to TMV.…”
Section: Mst Analysis Of Compounds To Tmv Cpmentioning
confidence: 99%